Breaking the sheep's back : the shocking true story of the decline and fall of the Australian wool industry - Massy, Charles (St Lucia, Queensland : University of Queensland Press, 2011)
From the author of the influential The Australian Merino comes the shocking true story of the decline and fall of the Australian wool empire a tale that features a brace of Australian characters, political skulduggery and betrayal on a massive scale. Breaking the Sheep's Back is the untold story of Australia's biggest business disaster.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Australian Wool Corporation; Sheep -- Government policy -- Australia; Sheep industry -- Government policy -- Australia; Corporations -- Corrupt practices -- Australia; Political corruption -- Australia; Electronic books